Wykorzystanie duoetnografii jako innowacyjnego podejścia w rozwijaniu refleksji przyszłych nauczycieli języka obcego - Werbińska, Dorota (Neofilolog, 2019)
Duo-ethnography is a research methodology, through which people of difference reconceptualise their histories of a particular phenomenon in juxtaposition with one another. Although initiated by researchers, duo- ethnographies can also be used as an innovative pedagogic tool that develops deep reflection in teacher candidates. After discussing the efficacy of duo-ethnography, a onesemester-long duo-ethnographic study is escribed, which was conducted by the author with six preservice English teachers. In the study, the participants worked in pairs (duo) and reflected on their own understandings of language teaching and learning (stage one), themselves as learners and future language teachers on the basis of the data from stage one (stage two), their conversational partners as learners and teachers on the basis of the data from stage one (stage three) and, finally, on the value of the duo-ethnographic project in language teacher preparation courses from their own perspective (stage four). The presentation ends with the author’s remarks about the project as a learning tool that undoubtedly encourages students to reflect but, on the other hand, has limitations that have to be acknowledged if duo- ethnography is employed as a pedagogic instrument in the classroom context.